AP2/DREB Transcription Factor RAP2.4 Activates Cuticular Wax Biosynthesis in Arabidopsis Leaves Under Drought - Yang, Sun Ui; Kim, Hyojin; Kim, Ryeo Jin; Kim, Jungmook; Suh, Mi Chung (Frontiers in Plant Science, 2020)
Drought is a critical environmental stress that limits growth and development of plants and reduces crop productivity. The aerial part of land plants is covered with cuticular waxes to minimize water loss. To understand the regulatory mechanisms underlying cuticular wax biosynthesis in Arabidopsis under drought stress conditions, we characterized the role of an AP2/DREB type transcription factor, RAP2.4. RAP2.4 expression was detected in one-week-old seedlings and rosette leaves, stems, stem epidermis, cauline leaves, buds, flowers, and siliques of 6-week-old Arabidopsis. The levels of RAP2.4 transcripts increased with treatments of abscisic acid (ABA), mannitol, NaCl, and drought stress. Under drought, total wax loads decreased by approximately 11% and 10%, and in particular, the levels of alkanes, which are a major wax component, decreased by approximately 11% and 12% in rap2.4-1 and rap2.4-2 leaves, respectively, compared with wild type (WT) leaves. Moreover, the transcript levels of cuticular wax biosynthetic genes, KCS2 and CER1, decreased by approximately 15–23% and 32–40% in rap2.4-1 and rap2.4-2 leaves, respectively, relative to WT 4 h after drought treatment, but increased by 2- to 12-fold and 3- to 70-fold, respectively, in three independent RAP2.4 OX leaves relative to WT. Epicuticular wax crystals were observed on the leaves of RAP2.4 OX plants, but not on the leaves of WT. Total wax loads increased by 1.5- to 3.3-fold in leaves of RAP2.4 OX plants relative to WT. Cuticular transpiration and chlorophyll leaching occurred slowly in the leaves of RAP2.4 OX plants relative to WT. Transcriptional activation assay in tobacco protoplasts showed that RAP2.4 activates the expression of KCS2 and CER1 through the involvement of the consensus CCGAC or GCC motifs present in the KCS2 and CER1 promoter regions. Overall, our results revealed that RAP2.4 is a transcription factor that activates cuticular wax biosynthesis in Arabidopsis leaves under drought stress conditions.